Diverse aims, challenges and opportunities for assessing outdoor learning: a critical examination of three cases from practice. Issue 1 (2nd January 2017) - Waite, Sue; Rutter, Orlando; Fowle, Adrian; Edwards-Jones, Andrew
Abstract : In this article, we consider the term 'assessment', its relationship to 'evaluation' and the implications for outdoor learning in the light of changing educational policy on assessment in England. A small-scale empirical study of how assessment was practised by two primary teachers on a residential trip and two further cases in practice are used to examine how emphases in assessment are shaped by contexts. Finally, we reflect on how conceptual frameworks that integrate planning, pedagogy and assessment might support assessment and evaluation practice in outdoor learning in a new era of apparent 'freedom' for teachers.